Memory Mates: A Classroom-Based Intervention to Improve Attention and Working Memory. (27th September 2013) - Davis, Nash; Sheldon, Linda; Colmar, Susan
<x content-type="archive" xml:space="preserve">Abstract</x> A small-scale research study was undertaken to identify the impact of attention and working memory (WM) strategies for one Year 3 class over four lessons. A selection of eight strategies was embedded in everyday mathematics lessons, and the class teacher was supported to adjust lesson delivery and monitor students experiencing WM overload. Explicit student and teacher instruction was provided to learn how to understand and apply the strategies during lessons. The goals of this research were to increase teacher expertise in teaching strategies to improve WM and to encourage students to practise and self-monitor strategy use. Students' academic engagement rose to 100% and all students increased their academic achievement outcomes.